Portfolio benefits of taxonomy orientated and renewable European electric utilities - Thomas Cauthorn; Christian Klein; Leonard Remme; Bernhard Zwergel (Journal of Asset Management, 2023)
This paper investigates carbon and energy mix risk in the equity prices of EU-Taxonomy orientated and renewable European electric utility companies. We calculate carbon intensity and energy mix factors to measure possible carbon and energy mix premia while investigating the performance of portfolios of EU-Taxonomy orientated and renewable European electric utilities. We use a unique dataset to extend the three-factor model presented by Fama and French (1993) and find evidence of a positive renewable energy mix premium for portfolios of EU-Taxonomy orientated firms and firms with a high level of renewable energy in the energy mix. A positive low-carbon premium is also found for these same portfolios. Lastly, based on the three-factor model, an EU-Taxonomy orientated portfolio outperforms both a non-orientated portfolio and a non-reporting portfolio while a renewable energy portfolio outperforms a conventional energy portfolio. Our results are important for regulators, investors and European electric utilities in assessing the impact environmental regulations have on a firm's cost of capital.
Keywords: G1; G11; G12; Q52; 330; Taxonomy; Factor model; Asset pricing; Renewable energy; Carbon risk; Carbon intensity